Nilai-Nilai Religius dalam Tembang Dolanan Anak sebagai Pembentuk Karakter Anak: Religious Values in Children's Toy Songs as Shaping Children's Characters - Suprapto; Arkam, Rohmad; Arifin, Moh. Zainul (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2025)
Indonesia is rich in culture, the importance of re-understanding the oral traditions of society. Instilling religious values ​​through tembang dolanan to build children's moral character is now a very urgent and unavoidable challenge and problem. Children's dolanan songs are local cultural wisdom as a medium for forming children's character. The purpose of this study is to describe and explain the religious values ​​contained in tembang dolanan as a form of children's character. The research design uses a descriptive-qualitative method, while the data collection technique uses a literature study. In this study, it was found first; that there are religious values ​​in children's tembang dolanan, these values ​​are in accordance with Javanese cultural norms. Religious values ​​in tembang dolanan have an influence on religious teachings, especially Islam. Second; using and instilling religious values ​​through tembang dolanan can help students get to know themselves, their own culture, and the culture of others, express language, find and use analytical and imaginative abilities that exist within themselves.